Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1152/ajpregu.00271.2010
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves rectal distension-induced delay in solid gastric emptying in dogs

Abstract: Yin J, Chen JD. Electroacupuncture improves rectal distensioninduced delay in solid gastric emptying in dogs. Am J Physiol Regul Integr Comp Physiol 301: R465-R472, 2011. First published May 18, 2011 doi:10.1152/ajpregu.00271.2010.-The aim of this study was to investigate the effects and mechanisms of electroacupuncture (EA) on rectal distension (RD)-induced delay in solid gastric emptying in dogs. Gastric emptying of solids was assessed in 12 dogs chronically implanted with a duodenal cannula by collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
(73 reference statements)
1
24
1
Order By: Relevance
“…However, a positive chronic and sustained effect is speculated. Although not investigated in the present study, EA has been shown to have sustained effects in other studies; for example, the liquid/solid gastric emptying was continuously accelerated after the termination of EA (40,49). Different from most of the other methods of electrical stimulation, such as cardiac stimulation and spinal cord stimulation with which stimulation has to be performed continuously, EA is typically performed once a day or a few times a day.…”
Section: Discussionmentioning
confidence: 77%
“…However, a positive chronic and sustained effect is speculated. Although not investigated in the present study, EA has been shown to have sustained effects in other studies; for example, the liquid/solid gastric emptying was continuously accelerated after the termination of EA (40,49). Different from most of the other methods of electrical stimulation, such as cardiac stimulation and spinal cord stimulation with which stimulation has to be performed continuously, EA is typically performed once a day or a few times a day.…”
Section: Discussionmentioning
confidence: 77%
“…In the two sessions with RD, RD was performed 60 -90 min after the meal. From preliminary studies, we observed that gastric emptying of solid was the fastest 60 -90 min after the meal and therefore RD was performed during that period (40). RD was achieved by the inflation of a latex balloon inserted into the rectum with 120 ml of air (6).…”
Section: Experimental Protocols Experiments 1: Assessment Of Complete mentioning
confidence: 99%
“…The entire precipitate of each collection was then taken out, placed in a paper plate, and dried in air for a few days until there were no changes in weight. The percentage of gastric emptying for each collection was calculated by using the following formula: % gastric emptying for each collection ϭ Wn/Wtϫ100%, where Wn was the dried weight of the collection and Wt was the total dried weight of all samples collected in the same dog in experiment 1 (40). This normalized percentage of gastric emptying compensated for any possible loss of ingested food, such as bypass of gastric chyme to the distal small intestine and any absorption that might have occurred before the collection from the duodenal cannula.…”
Section: Measurements and Analysesmentioning
confidence: 99%
“…7 EA at both PC6 and ST36 or ST36 alone also accelerated gastric emptying in dogs with delayed gastric emptying induced by duodenal distention 8 or rectal distention. 23 A typical example showing the effect and mechanism of EA on rectal distention-induced delay in gastric emptying is presented in Fig. 3.…”
Section: Electroacupuncture and Gastric Emptyingmentioning
confidence: 99%